2021
DOI: 10.3389/fphys.2021.684532
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Dibutyl Phthalate and Reproductive-Related Outcomes in Animal Models: Evidence From Rodents Study

Abstract: Background: Dibutyl phthalate (DBP) was an endocrine disruptor, which may lead to cancer and affects reproductive function when accumulated in the body. But the precise role of DBP in the reproductive system remained controversial.Objective: We employed the meta-analysis to explore the relationship between DBP and reproductive-related outcomes.Methods: We searched relevant literature in PubMed, EMBASE, and Web of Science databases. The standardized mean differences (SMDs) and their 95% CIs were measured by ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…We observed increased levels in both treatment groups, suggesting that a disruption of enzyme function could be due to reactive species production. This is in accordance with several studies showing that phthalates elicit oxidative stress [ 10 , 12 ] and disrupt steroidogenesis [ 9 , 10 , 18 ]. However, more studies are necessary to fully elucidate how DBP exposure is affecting the steroidogenic enzymes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed increased levels in both treatment groups, suggesting that a disruption of enzyme function could be due to reactive species production. This is in accordance with several studies showing that phthalates elicit oxidative stress [ 10 , 12 ] and disrupt steroidogenesis [ 9 , 10 , 18 ]. However, more studies are necessary to fully elucidate how DBP exposure is affecting the steroidogenic enzymes.…”
Section: Discussionsupporting
confidence: 93%
“…Several in vivo toxicological studies have also shown that DBP is an endocrine disruptor, mainly by reducing testosterone levels, and that DBP exposure affects reproductive health by, for example, reducing semen motility and production [ 7 , 8 ]. Despite these previous studies on the effects of DBP exposure [ 7 , 9 ], there are still important knowledge gaps regarding the mechanisms behind these effects.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effects of the studied compounds may reflect a physiological adaptation of P. aeruginosa upon exposure. Several Pseudomonas species, which have been isolated from contaminated soils such as industrial mining areas or intensive crop lands [38], are indeed able to metabolize phthalates, including DBP [57,58], which is one of the most toxic phthalic acid esters [59]. This ability is of particular interest in terms of bioremediation and soil decontamination [60].…”
Section: Discussionmentioning
confidence: 99%
“…MnBP is known to exert antiandrogenic actions in male ,, and female reproductive organs. , However, interspecies differences in glucocorticoids precluded us from comparing our MnBP results to the rodent studies available. , Since comparison with other epidemiological studies is neither possible, the MnBP-related increase in 11-dehydrocorticosterone levels among women carrying male fetuses is difficult to interpret and needs to be confirmed in future studies.…”
Section: Discussionmentioning
confidence: 94%